Peningkatan Kompetensi Profesional Guru PAI dalam Menghadapi Generasi Alpha Abad ke-21 - Wildan Fahmi Febriansyah; Muhammad Fahmi; Fathur Rohman (Jurnal Pendidikan Islam, 2024)
The development of technology and information must be accompanied by the improvement of teachers' competencies. Teacher competence refers to a set of skills that teachers or educators must possess to perform their duties accurately and effectively. If an Islamic Education (PAI) teacher lacks competence, it will be challenging to achieve learning objectives, especially when dealing with Generation Alpha in the 21st century. This study aims to understand how Islamic Education teachers at SMPN 5 Surabaya improve their competencies to face Generation Alpha in the 21st century. The research method used is qualitative, along with library research, utilizing journals and books. The research design employs a case study, and data collection tools include observations and interviews. Based on the findings, it was discovered that PAI teachers at SMPN 5 Surabaya are certified. However, there are still deficiencies in the teachers’ skills or strategies to enhance their competencies to effectively engage with Generation Alpha in the 21st century. In addition, external challenges, such as time and learning facilities, were identified, highlighting the need to find appropriate strategies for improving PAI teachers’ competencies and addressing external issues to achieve the expected learning outcomes in line with technological advancements.